Feasibility of an Inversion Recovery-Prepared Fat-Saturated Zero Echo Time Sequence for High Contrast Imaging of the Osteochondral Junction - Jang, Hyungseok; Ma, Yajun; Carl, Michael; Lombardi, Alecio F.; Chang, Eric Y.; Du, Jiang (Frontiers in Endocrinology, 2021)
Purpose: The osteochondral junction (OCJ) region—commonly defined to include the deep radial uncalcified cartilage, tidemark, calcified cartilage, and subchondral bone plate—functions to absorb mechanical stress and is commonly associated with the pathogenesis of osteoarthritis. However, magnetic resonance imaging of the OCJ region is difficult due to the tissues’ short transverse relaxation times (i.e., short T2 or T2*), which result in little or no signal with conventional MRI. The goal of this study is to develop a 3D adiabatic inversion recovery prepared fat saturated ZTE (IR-FS-ZTE) sequence for high-contrast imaging of the OCJ. Method: An IR-FS-ZTE MR sequence was developed to image the OCJ on a clinical 3T MRI scanner. The IR-FS-ZTE sequence employed an adiabatic inversion pulse followed by a fat saturation pulse that suppressed signals from the articular cartilage and fat. At an inversion time (TI) that was matched to the nulling point of the articular cartilage, continuous ZTE imaging was performed with a smoothly rotating readout gradient, which enabled time-efficient encoding of the OCJ region’s short T2 signal with a minimal echo time (TE) of 12 μs. An ex vivo experiment with six cadaveric knee joints, and an in vivo experiment with six healthy volunteers and three patients with OA were performed to evaluate the feasibility of the proposed approach for high contrast imaging of the OCJ. Contrast-to-noise ratios (CNRs) between the OCJ and its neighboring femoral and tibial cartilage were measured. Results: In the ex vivo experiment, IR-FS-ZTE produced improved imaging of the OCJ region over the clinical sequences, and significantly improved the contrast compared to FS-ZTE without IR preparation (p = 0.0022 for tibial cartilage and p = 0.0019 for femoral cartilage with t-test). We also demonstrated the feasibility of high contrast imaging of the OCJ region in vivo using the proposed IR-FS-ZTE sequence, thereby providing more direct information on lesions in the OCJ. Clinical MRI did not detect signal from OCJ due to the long TE (>20 ms). Conclusion: IR-FS-ZTE allows direct imaging of the OCJ region of the human knee and may help in elucidating the role of the OCJ in cartilage degeneration.